India in early modern English travel writings: protestantism, enlightenment, and toleration - Banerjee, Rita (Studies in medieval and reformation traditions, 2021)
Comparing the variant ideologies of the representations of India in seventeenth-century European travelogues, India in Early Modern English Travel Narratives concerns a relatively neglected area of study and often overlooked writers. Relating the narratives to contemporary ideas and beliefs, Rita Banerjee argues that travel-writers, many of them avid Protestants, seek to negativize India by constructing her in opposition to Europe, the supposed norm, by deliberately erasing affinities and indulging in the politics of disavowal. However, some travelogues show a neutral stance by dispassionate ethnographic reporting, indicating a growing empirical trend. Yet others, influenced by the Enlightenment ideas of diversity, demonstrate tolerance of alien practices and, occasionally, acceptance of the superior rationality of the other's customs